Learning in an Online Distance Education Course: Experiences of Three International Students - Zhang, Zuochen; Kenny, Richard F. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
This case study explores the learning experiences of three international students who were enrolled in an online master’s program offered by a large university in Canada. The aim of the study was to understand the international students’ experiences with, and perspectives on, the online learning environment. Findings indicate that previous education and especially language proficiency strongly impacted the learning of these students in this environment. Non-native English speakers required considerably more time to process readings and postings and to make postings themselves. Their lack of familiarity with the details of North American culture and colloquial language made it difficult to follow much of the course discussion. They also tended to avoid socializing in the course, which left them at the periphery of course activities. Based on these findings, the authors make the following recommendations for designers and instructors of online courses: 1) Raise the English language proficiency requirement for graduate admissions into online programs because the text-based communication in a CMC space requires interpreting messages without non-verbal cues; 2) Ensure that online distance education course designers are aware of the needs and expectations of international students; and 3) Combine the design principles from both traditional and constructivism theories.